2007
DOI: 10.2172/915387
|View full text |Cite
|
Sign up to set email alerts
|

Design of the ILC Crab Cavity System

Abstract: The International Linear Collider (ILC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The modes at 8.02 GHz are the π and 8π/9 modes of the 5 th dipole passband. Numerical simulations using the finite difference code, MAFIA [6], have previously shown that these modes are expected to have high loss factors [2]. The largest of these peaks was calculated to have an R/Q of 11.6 Ω/cm 2 which is in excellent agreement with the mean R/Q measured at a wire offset of 1mm for this mode.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The modes at 8.02 GHz are the π and 8π/9 modes of the 5 th dipole passband. Numerical simulations using the finite difference code, MAFIA [6], have previously shown that these modes are expected to have high loss factors [2]. The largest of these peaks was calculated to have an R/Q of 11.6 Ω/cm 2 which is in excellent agreement with the mean R/Q measured at a wire offset of 1mm for this mode.…”
Section: Discussionsupporting
confidence: 65%
“…A numerical study carried out on the cavity identified a number of modes that have significant loss factors [2] and therefore would require significant damping. In order to verify the impedances calculated by the numerical simulations, a modular aluminium model of the cavity was constructed.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The crab cavity needs ∼ 3 kW per cavity for about 10 msec, with a Q ext of ∼ 10 6 [196][197][198]201]. The crab cavity is placed in a cryostat with tuner,…”
Section: Crab Cavity Systemmentioning
confidence: 99%
“…The ILC design foresees a horizontal crossing angle of 14 mrad between the e − and the e + beamlines at the IP. In order to maximise the luminosity, the bunches are correspondingly rotated by 7 mrad using crab cavities [15]. The collider experiments at the IP contain two types of magnets which also influence the beams.…”
Section: Beam Parameters and Interaction Regionmentioning
confidence: 99%